Bis[pyrrolyl Ru(ii)] triads: a new class of photosensitizers for metal–organic photodynamic therapy. Issue 44 (21st October 2020) - Smithen, Deborah A.; Monro, Susan; Pinto, Mitch; Roque, John; Diaz-Rodriguez, Roberto M.; Yin, Huimin; Cameron, Colin G.; Thompson, Alison; McFarland, Sherri A.
Abstract : Ten dinuclear Ru(ii ) complexes based on the bis[pyrrolyl Ru(ii )] triad scaffold were prepared to evaluate the influence of the central organic linker on the spectroscopic and in vitro photodynamic therapy (PDT) properties of the compounds. Abstract : A new family of ten dinuclear Ru(ii ) complexes based on the bis[pyrrolyl Ru(ii )] triad scaffold, where two Ru(bpy)2 centers are separated by a variety of organic linkers, was prepared to evaluate the influence of the organic chromophore on the spectroscopic and in vitro photodynamic therapy (PDT) properties of the compounds. The bis[pyrrolyl Ru(ii )] triads absorbed strongly throughout the visible region, with several members having molar extinction coefficients ( ε ) ≥ 10 4 at 600–620 nm and longer. Phosphorescence quantum yields ( Φ p ) were generally less than 0.1% and in some cases undetectable. The singlet oxygen quantum yields ( Φ Δ ) ranged from 5% to 77% and generally correlated with their photocytotoxicities toward human leukemia (HL-60) cells regardless of the wavelength of light used. Dark cytotoxicities varied ten-fold, with EC50 values in the range of 10–100 μM and phototherapeutic indices (PIs) as large as 5400 and 260 with broadband visible (28 J cm −2, 7.8 mW cm −2 ) and 625 nm red (100 J cm −2, 42 mW cm −2 ) light, respectively. The bis[pyrrolyl Ru(ii )] triad with a pyrenyl linker (5h ) was especially potent, with an EC50 value of 1 nM and PI > 27 000 with visible light and subnanomolar activity with 625 nm light (100 J cm −2, 28 mW cm −2 ). The lead compound 5h was also tested in a tumor spheroid assay using the HL60 cell line and exhibited greater photocytotoxicity in this more resistant model (EC50 = 60 nM and PI > 1200 with 625 nm light) despite a lower dark cytotoxicity. The in vitro PDT effects of 5h extended to bacteria, where submicromolar EC50 values and PIs >300 against S. mutans and S. aureus were obtained with visible light. This activity was attenuated with 625 nm red light, but PIs were still near 50. The ligand-localized 3 ππ* state contributed by the pyrenyl linker of 5h likely plays a key role in its phototoxic effects toward cancer cells and bacteria.